2022
DOI: 10.1590/1807-3107bor-2022.vol36.0009
|View full text |Cite
|
Sign up to set email alerts
|

Using a professional DSLR camera to measure total shrinkage of resin composites

Abstract: This study evaluated the optical method for measuring free total shrinkage using a Digital Single Lens Reflex (DSLR) camera. Eight composites were evaluated, conventional, bulk fill and low-shrinkage: Z100 (3M Oral Care), Gradia Direct Anterior (GC corporation), Spectra Smart (Dentsply), Filtek Z350 XT (3M Oral Care), Aura Bulk Fill (SDI), Vittra APS (FGM), Opus Bulk Fill APS (FGM), and Beautifil II LS (Shofu Inc.). The samples (6 mm diameter and 1.5 mm thick, n = 10) were placed on a polyvinylsiloxane impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Limited research and information are available on the mechanical, spectral, and structural properties of seven different SsURCs. Color adjustment potential [19,20], shade match [21], optical behavior [22], color stability [1], cytotoxicity [23], F S , and E M [24,25] of Omnichroma; quasi-static and viscoelastic behavior [26] of Charisma Diamond and Omnichroma; shrinkage [27], color change, surface roughness [28], micro-hardness [29] and contrast ratio of Vittra APS; color stability [30], F S and depth of cure [31] of Optishade; color stability, surface properties [1,32], shrinkage stress, E M [33] and DC [34] of Admira fusion X-tra; F S , E M , [35], color stability [36][37][38] of Essentia have been evaluated and investigated in previous research [19,24,38].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research and information are available on the mechanical, spectral, and structural properties of seven different SsURCs. Color adjustment potential [19,20], shade match [21], optical behavior [22], color stability [1], cytotoxicity [23], F S , and E M [24,25] of Omnichroma; quasi-static and viscoelastic behavior [26] of Charisma Diamond and Omnichroma; shrinkage [27], color change, surface roughness [28], micro-hardness [29] and contrast ratio of Vittra APS; color stability [30], F S and depth of cure [31] of Optishade; color stability, surface properties [1,32], shrinkage stress, E M [33] and DC [34] of Admira fusion X-tra; F S , E M , [35], color stability [36][37][38] of Essentia have been evaluated and investigated in previous research [19,24,38].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the bond strength, the different types of composites did not influence the results obtained. It is noteworthy that both were applied according to the manufacturers' recommendations, that is, the conventional one by the incremental technique and the bulk-fill by the single-increment technique, which may have compensated for the fact that the conventional composite presented a very high polymerization shrinkage, higher than bulk-fill [49]. Other studies [50,51] also found similar bond strength values between bulk-fill and conventional composites when applied by the recommended techniques.…”
Section: Discussionmentioning
confidence: 91%
“…The use of bulk-fill and conventional composites in this study was based on differences regarding the polymerization shrinkage [49] of both and, consequently, on the behavior that they could develop related to the shrinkage stresses generated at the bonding interface in cavities of high cavity configuration factor (Class I). Regarding the bond strength, the different types of composites did not influence the results obtained.…”
Section: Discussionmentioning
confidence: 99%